Feeding practices according to the WHO- recommendations for HIV exposed children in northwest Ethiopia: A cross-sectional study. (December 2018) - Esubalew, Frizer; Atenafu, Azeb; Abebe, Zegeye
Summary: Background: Malnutrition is a major problem for HIV exposed children, which is mainly caused by inappropriate feeding practice. Hence, the study aimed to assess adherence to optimal complementary feeding practices recommended by the WHO and associated factors among HIV exposed infants and young children aged 6–18 months in selected Amhara Regional Hospitals, northwest Ethiopia. Methods: An institution based cross-sectional study was conducted from March 10 to April 30, 2017. Systematic random sampling was employed to select study participants. A 24hr dietary recall was used to assess compliance with child optimal complementary feeding practice. Children were considered to have received optimal complementary feeding when they fulfill the criteria of the timely introduction of solid, semi-solid or soft foods, and minimum acceptable diet. Both bi-variable and multivariable binary logistic regression analysis were applied to identify factors associated with optimal complementary feeding practice. Results: In this study, about 25.5% of HIV exposed children received optimal complementary feeding. More than two thirds, (70.7%), and more than a third, (36.9%), of the children received the recommended meal frequency and minimum acceptable diet, respectively. Father's education; primary (AOR = 2.39; 95%CI: 1.18, 4.88) and higher (AOR = 2.44; 95%CI: 1.37, 4.34), rich household wealth status (AOR = 2.08; 95%CI: 1.13, 3.82), and satisfactory media exposure (AOR = 1.70; 95%CI: 1.04, 2.78), and mothers disclosing that they have HIV (AOR = 1.78; 95%CI: 1.07, 2.98) were positively associated with optimal feeding practices. Conclusion: Optimal complementary feeding practice was not at the level recommended by the WHO. Household wealth status, mother's HIV disclosure, and paternal educational status were positively associated with optimal complementary feeding practices among HIV exposed children. Therefore, a social safety net program for HIV positive mothers is recommended. In addition, strengthening maternal counseling about disclosure of HIV status and increased media promotion of optimal child feeding is important to achieve the recommended feeding goals.